2017
DOI: 10.1200/jco.2017.35.4_suppl.523
|View full text |Cite
|
Sign up to set email alerts
|

Sidedness matters: Surrogate biomarkers prognosticate colorectal cancer upon anatomic location.

Abstract: 523 Background: Recent evidence indicate that the anatomic location of primary tumors across the colon correlate with survival in the metastatic setting, whereas left-sided tumors may exhibit superior survival compared with right-sided. The Oncotype DX, a 12-gene colon cancer assay, is a clinically validated predictor of recurrence risk in stage II colorectal cancer (CRC) patients. Previous studies had indicated that CDX2-negative colorectal tumors are often associated with several adverse prognostic variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…We found that the incidence of postoperative recurrence for left colon cancer was higher than that of right, and left colon is one of the independent risk factors of poorer DFS, which was consistent with some reports [13,14]. The majority of the literature differs, reporting that there is no difference [15] or that the right colon has a relatively poor prognosis [16][17][18][19]. The inclusion of the rectum in the left colon is the biggest difference between these reports.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the incidence of postoperative recurrence for left colon cancer was higher than that of right, and left colon is one of the independent risk factors of poorer DFS, which was consistent with some reports [13,14]. The majority of the literature differs, reporting that there is no difference [15] or that the right colon has a relatively poor prognosis [16][17][18][19]. The inclusion of the rectum in the left colon is the biggest difference between these reports.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies that included patients with nonmetastatic disease obtained different results for patients with CS I and II. However, these studies have consistently demonstrated the negative impact of right‐sided colon tumors in patients with CS III …”
Section: Introductionmentioning
confidence: 99%